2019
DOI: 10.3389/fphar.2019.01177
|View full text |Cite
|
Sign up to set email alerts
|

International Normalized Ratio as a Screening Test for Assessment of Anticoagulant Activity for Patients Treated With Rivaroxaban or Apixaban: A Pilot Study

Abstract: Introduction: In patients treated with direct oral anti activated factor X (anti-FXa) anticoagulants such as apixaban and rivaroxaban, there are several emergency and non-emergency conditions in which anticoagulation activity should be measured. The validity of the common global clotting tests, prothrombin time and international normalized ratio (PT/INR) for determination of blood levels of these drugs, has been widely investigated. As the anticoagulation activity evaluation “calibrated anti-FXa” of these drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Although there were no previous studies comparable to this one, the current findings are basically consistent with those in 2 relevant previous studies. 13 , 14 In the study of Kodato et al, a lower INR level was associated with a higher risk of DVT occurrence in patients receiving edoxaban thromboprophylaxis, 13 being similar with our study except ours targeted VTE recurrence. In the study of Ofek et al, there was a strong correlation between INR level and anti-Xa concentrations which is used to monitor DOACs anticuagulation, in patients receiving rivaroxaban for the prevention and treatment of VTE.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Although there were no previous studies comparable to this one, the current findings are basically consistent with those in 2 relevant previous studies. 13 , 14 In the study of Kodato et al, a lower INR level was associated with a higher risk of DVT occurrence in patients receiving edoxaban thromboprophylaxis, 13 being similar with our study except ours targeted VTE recurrence. In the study of Ofek et al, there was a strong correlation between INR level and anti-Xa concentrations which is used to monitor DOACs anticuagulation, in patients receiving rivaroxaban for the prevention and treatment of VTE.…”
Section: Discussionsupporting
confidence: 87%
“…A formula by using INR values that estimated the anticoagulant activity of rivaroxaban was developed and then validated. 14 These studies have confirmed that INR has a predictive role for the anticoagulant efficacy in patients who receive DOACs anticoagulation. As such, we hypothesized that maybe INR had certain role in the prediction of VTE recurrence and bleeding for patients with acute VTE who undergo anticoagulation with DOACs.…”
Section: Introductionmentioning
confidence: 75%
“…However, inter‐device variations in the PT make it difficult to compare among different institutions 29 . The international normalized ratio (INR) refers to the ratio of prothrombin time to the normal prothrombin time 30 and is regarded as an ideal method for judging the anticoagulation effect 31 . It overcomes the variability among different laboratories by thromboplastin sensitivity 32 .…”
Section: Introductionmentioning
confidence: 99%
“…Rivaroxaban belongs to a group of medicines called antithrombotic agents. They are used as an inhibitor of factor Xa, which plays a role in blood clotting [ 1 ]. The administration of this novel antithrombotic agent is recommended following the use of anticoagulant drugs, such as warfarin, and it does not require international normalized ratio monitoring [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%